Experimental Investigation on the Kinetic Parameters of Diffusion Component for Vacuum Brazing SS316L/BNi-2/SS316L Joint. (2015) - Liu, Z.P.; Zhou, G.-Y.; Tian, F.Q.; Chen, D.Q.; Tu, S.-T.
Abstract: High temperature vacuum brazing has become the only appropriate process for thin-walled structures such as compact heat exchangers used in high-temperature gas-cooled reactor (HTGR) systems. During the typical brazing process, major attention should be paid to the isothermal solidification stage which has the most important influence on joint quality. However, the isothermal solidification process is controlled by the diffusion behavior of melting point depressant (MPD) elements, and only thorough diffusion of MPD elements into the base metal can result in the formation of the full solid-solution brazed joints. Therefore, it is significant for brazed joints to accurately obtain the kinetic parameters of diffusion component. In this study, a new type of wedge-shaped brazing specimen was proposed to study the joints properties. The experiments were carried out on the combination of SS316L with BNi-2 filler alloy at 1050, 1075 and 1100 °C with different holding time ranged from 15 to 45 min, respectively. Two classical models coupled with experimental data have been used to determine the kinetic parameters, including diffusion coefficient and diffusion activity energy. Then the effects of the brazing temperature and holding time on the maximum brazing clearance (MBC) value are also investigated. The results show that the diffusion coefficient increases with the increase of temperature and decreases with the increase of holding time at constant temperature. The diffusion activity energy of boron in SS316L is 134 kJ/mol. Meanwhile, significant augment of the MBC value has also been observed with increase in brazing temperature and holding time.